Патоморфоз аутоімунних захворювань щитоподібної залози у Прикарпатському ендемічному зобному регіоні - Поспішіль, Ю. О.; Вовк, В. І.; Якимець, Н. С. (Clinical Endocrinology and Endocrine Surgery, 2008)
The analysis of results of histological examinations of postoperative material of 7925 patients operated on account of thyroid diseases in Lvov Regional Clinical Hospital during 1991-2005 years was made. Absolute number of patients operated on account of autoimmune thyroid diseases in 1991-2005 years in comparison to previous years was increased. A structure of autoimmune diseases was changed. Among total cases of autoimmune thyroid diseases Hashimoto thyroiditis dominates in 1981-1990 years while focal thyroiditis dominates in 1991-2005 years. In one third of cases autoimmune thyroid diseases together with others thyroid diseases, most often with nontoxic multinodular goiter, follicular adenoma and papillary carcinoma, in the same patients were found.